DINAMIKA ORBIT ASTEROID YANG ANALOG DENGAN ORBIT BUMI - - B. Dermawan; - T. Hidayat; - M. Putra; - A. Fermita; - D. T. Wahyuningtyas; - D. Mandey; - Z. Hudaya; - D. Utomo (Jurnal Sains Dirgantara, 2010)
A set of asteroids that belong to Atens and Apollos groups which orbits are crossing the Earth at 1 AU is known as Earth-like-Orbit Asteroids. As of 1 July 2009, there were 19 Earth-like-Orbit Asteroids listed at the JPL (Jet Propulsion Laboratory – NASA) Small-Body Database. Orbital dynamics of five new asteroids among them (2008 EV5, 2008 JE, 2008 KT, 2008 UA202, and 2008 UC202) have not been studied yet. This study is important because they are asteroids belonging to potentially hazardous objects. High accuracy orbital integrations for a time-span of –1000 to +1000 yr have been conducted to figure out their evolutionary tracks. Our results show that high inclination Earth-like-Orbit Asteroids of more than ~5 degrees tend to be more dynamically stable than those of lower orbital inclination which often switch over from Atens to Apollos and vice versa. Four new Earth-like-Orbit Asteroids are found to have potential collisions with Earth because they will encounter the Earth at minimum distances of less than 0.01 AU. Keywords: Asteroids, Orbit dynamics, Hazardous objects